(untitled) - Griffin, Ronald C (Cambridge, Mass, 2006)
The book focuses on the scarcity of water quantity (rather than water quality). The author presents the economic theory of resource allocation, recognizing the peculiarities imposed by water, and expands the theory to encompass time-defined matters such as ground water depletion. He then discusses such subjects as institutional economics, water law, how economics is used in policy and cost-benefit analysis, the roles of water marketing and water pricing, demand and supply estimation, privatization, and modeling with demand and supply functions
Keywords: Water resources development,Water resources development,Water-supply,Phát triển nguồn nước,Phát triển nguồn nước,Cung cấp nước; Economic aspects,Government policy,Economic aspects,Khía cạnh kinh tế,Chính sách nhà nước,Khía cạnh kinh tế